Adult and Pediatric Lateral Lamella Cribriform Plate Height: In Need for a Comparative Study - Sakandar, Gilbert (Allergy Rhinol (Providence), 2019)
Surgery for sinuses has evolved with the advancement of instruments and modification in techniques. Endoscopes have expanded the surgical roles for lesions in the nose and para-nasal sinuses with reduced rate of complications and cosmetic side effects. Nevertheless sinus surgery in pediatrics patients has its own challenges. Pre-operative imaging is of paramount important especially when embarking on skull base procedures. The differences between adult and pediatric anatomy need to be further studied.